2019
DOI: 10.4103/jpn.jpn_2_19
|View full text |Cite
|
Sign up to set email alerts
|

Mild phenotype associated with SLC6A1 gene mutation: A case report with literature review

Abstract: A bstract The Solute Carrier Family 6 Member 1 ( SLC6A1 ) gene encodes the gamma-aminobutyric acid (GABA) transporter 1, which is one of the main GABA transporters. The clinical picture of SLC6A1 gene mutations is characterized by a broader spectrum including a mild-to-moderate intellectual disability, speech difficulties, behavioral problems, epilepsy (often with myoclonic-atonic and atypical absence seizures, characterizing a myoclonic-at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…Finally, focusing on the treatment to improve epilepsy in our patients, administration of VPA has given a good response. These results of the treatment with VPA are similar to those obtained in patients with other SLC6A1 variants [ 2 , 41 ].…”
Section: Discussionsupporting
confidence: 84%
“…Finally, focusing on the treatment to improve epilepsy in our patients, administration of VPA has given a good response. These results of the treatment with VPA are similar to those obtained in patients with other SLC6A1 variants [ 2 , 41 ].…”
Section: Discussionsupporting
confidence: 84%
“…After reports of SLC6A1 variants in patients with myoclonic atonic epilepsy (Dikow et al, 2014;Carvill et al, 2015;Mattison et al, 2018;Cai et al, 2019;Posar and Visconti, 2019), clinical, neurophysiological, and genetic examination of a relatively large cohort of subjects (n = 34) bearing SLC6A1 mutations demonstrated that 97% of them exhibited varying degrees of intellectual disability (ID) and that 91% had been diagnosed with epilepsy (absence, myoclonic, or atonic) based on EEG patterns characterized by irregular, high, ample, generalized spikes, and wave discharges (Johannesen et al, 2018). Notably, more than 60% of these subjects had suffered from moderate or significant ID before epilepsy onset, whereas in a limited number of cases, the ID was not accompanied by epilepsy.…”
Section: Recent Studies Suggest a Less Simplistic Scenariomentioning
confidence: 99%
“…Of the >100 GAT1 variants deposited in the ENSEMBL database, 45 point mutations (including 12 frameshift/truncating and 28 missense) are displayed in Fig. 3g and Table 3 ( Cai et al, 2019 ; Carvill et al, 2015 ; Halvorsen et al, 2015 ; Islam et al, 2018 ; Johannesen et al, 2018 ; Mattison et al, 2018 ; Palmer et al, 2016 ; Posar & Visconti, 2019 ; Rauch et al, 2012 ; Wang et al, 2020 ; Zech et al, 2017 ). The mutations are linked to impaired cognitive development, several epileptic seizure types and mild to moderate ID (mostly language impairment) in the afflicted individuals.…”
Section: Slc6 Family: Monogenic Diseases Associated With Tra...mentioning
confidence: 99%